The AMTE handbook of mathematics teacher education : reflection on past, present and future : paving the way for the future of mathematics teacher education - Benken, Babette M. (AMTE professional book series ;, 2024)
"This new volume of the Association of Mathematics Teacher Education's (AMTE) Professional Book Series is a critical and timely resource that paves the way and guides the future of mathematics teacher education. The collection of work in this AMTE Handbook for Mathematics Teacher Education reflects on research and what we know about how best to prepare and support both mathematics teachers and mathematics teacher educators and presents what is happening in the field. Examples included in the 22 chapters highlight how we are preparing teachers across multiple contexts (e.g., within district, in content courses for the major) and grade ranges (K-20+) and all chapters highlight relevant connections to the AMTE Standards for Preparing Teacher of Mathematics. Most importantly, it explores what we do not yet fully understand and where we are going-in essence, how we can move the field forward. The 95 contributing authors range from graduate students to those who have served as leaders in the field in multiple ways for many years. Authors include K-12 teachers, school administrators, district leaders, graduate students, higher education faculty, and professional development facilitators"--